Peran Technostress terhadap Performa Kinerja Karyawan di Era Digital - Griselda Yuliawan; Vilia Chandra; Zamralita Zamralita; Reza Fahlevi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2026)
The rapid advancement of digital technology has improved work efficiency but may also increase technostress, potentially affecting employee performance. This study aimed to examine the effect of technostress on employee performance in the digital era. A quantitative approach with a descriptive correlational and cross-sectional design was employed. The study involved 127 employees selected using purposive sampling. Data were collected using the Digital Stressors Scale (DSS) to measure technostress and the Individual Work Performance Questionnaire (IWPQ) to assess employee performance. The data were analyzed using simple linear regression. The findings revealed that technostress did not have a significant effect on employee performance (β = -0.089, p = 0.321 > 0.05), with a coefficient of determination (R²) of 0.008. These results indicate that technostress is not a primary determinant of employee performance. Other factors, such as digital competence, adaptability, and organizational support, are likely to contribute more substantially to employee performance